1994
DOI: 10.1177/000992289403301113
|View full text |Cite
|
Sign up to set email alerts
|

Permanently Damaged: Long-Term Follow-Up of Shaken Babies

Abstract: Shaken baby syndrome (SBS) is a term denoting a particularly harmful form of child abuse. By definition, 1 these infants have intracranial and retinal hemorrhages in the absence of signs of head trauma or skull fracture. Most SBS victims appear to have significant neurologic damage at the time of diagnosis.2,3 The medical literature, however, does not describe these children as they grow older. A 1986 article4 called for follow-up studies on these children, but a computerized literature search turned up only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Even on admission CT scans, signs of pre-existing brain abnormality were present in nearly one-third of children with acute inflicted brain injury who had no history of prior injury. Children with inflicted TBI have unfavorable long-term cognitive and motor outcomes [12,15] and are more severely disabled than children with noninflicted TBI of comparable severity [14]. The poorer developmental outcomes in children with inflicted TBI probably reflect a combination of prior occult brain injury, the current brain injury, and unfavorable environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Even on admission CT scans, signs of pre-existing brain abnormality were present in nearly one-third of children with acute inflicted brain injury who had no history of prior injury. Children with inflicted TBI have unfavorable long-term cognitive and motor outcomes [12,15] and are more severely disabled than children with noninflicted TBI of comparable severity [14]. The poorer developmental outcomes in children with inflicted TBI probably reflect a combination of prior occult brain injury, the current brain injury, and unfavorable environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, surface injuries that were consistent with intentional injuries were present in about one sixth of the children whose injuries were attributed to accidental causes, suggesting that the actual number of intentional injuries may be far greater. Fischer and Allasio (1994) traced the records of 25 SBS infants. Ewing-Cobbs et al (1998) found 45% of children surviving brain injury resulting from violence to be mentally retarded compared to only 5% of those surviving accidental injury.…”
Section: Direct Effects Of Traumamentioning
confidence: 99%
“…In the acute period children with inflicted injuries tend to be symptomatic and have a higher frequency of cerebral oedema, anoxic/ischaemic damage (2,6,7), which supports the hypothesis that children with inflicted injuries have a delayed presentation that partially explains their high morbidity rate (6). The morbidity rate in different studies among survivors has varied from 38–40% (9–11) to 58–70% (12–16). Some studies report the morbidity rate to be as high as 80–100% among survivors (7,17–19).…”
Section: Introductionmentioning
confidence: 99%